Justice as a Dominant of the Legal Order Overview of the Fourth Baskin Readings Conference (Saint Petersburg, November 2, 2022) - N. V. Razuvaev; I. K. Shmarko (Теоретическая и прикладная юриспруденция)
This article provides an overview of the Fourth Baskin Readings conference organized by the North-Western Institute of Management of the RANEPA. The conference was devoted to the problem of justice in law. The participants considered the problems of determining the content of the concept of  justice, its criteria, the problems of justice in various branches of law and science, and also suggested options for formulating such criteria in relation to different situations.